Remarkable new fossil species of Schistostoma Becker (Diptera: Dolichopodidae: Microphorinae) from mid-Cretaceous Burmese amber - Brooks, Scott E.; Cumming, Jeffrey M.; Grimaldi, David A. (Zootaxa, 2019)
Two closely related and distinctive species of Schistostoma Becker, i.e. Schistostoma burmanicum sp. nov. and Schistostoma foliatum sp. nov., are described from two male specimens preserved in mid-Cretaceous Burmese amber and recorded as the first known fossil representatives of this extant genus of Microphorinae. Both species possess greatly enlarged lamellate fore tibiae and modified leg chaetotaxy that are presumably male secondary sexual features. The generic limits of Schistostoma are briefly discussed and a rationale for the inclusion of these new species is provided.